Stakeholder participation in the COVID-19 pandemic preparedness and response plans: A synthesis of findings from 70 countries (2024)
ABSTRACT: Stakeholder participation is a key component of a fair and equitable priority-setting in health. The COVID-19 pandemic highlighted the need for fair and equitable priority setting, and hence, stakeholder participation. To date, there is limited literature on stakeholder participation in the development of the pandemic plans (including the priority setting plans) that were rapidly developed during the pandemic. Drawing on a global study of national COVID-19 preparedness and response plans, we present a secondary analysis of COVID-19 national plans from 70 countries from the six WHO regions, focusing on stakeholder participation. We found that most plans were prepared by the Ministry of Health and acknowledged WHO guidance, however less than half mentioned that additional stakeholders were involved. Few plans described a strategy for stakeholder participation and/or accounted for public participation in the plan preparation. However, diverse stakeholders (including multiple governmental, non-governmental, and international organizations) were proposed to participate in the implementation of the plans. Overall, there was a lack of transparency about who participated in decision-making and limited evidence of meaningful participation of the community, including marginalized groups. The critical relevance of stakeholder participation in priority setting requires that governments develop strategies for meaningful participation of diverse stakeholders during pandemics such as COVID-19, and in routine healthcare priority setting.